2020
DOI: 10.1007/s12178-020-09607-1
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Patellofemoral Instability in the Pediatric Patient: Management and Pitfalls

Abstract: Purpose of Review The purpose of the review is to discuss the relevant pathoanatomy, management, complications, and technical considerations for recurrent patellofemoral instability (PFI) in the pediatric population. Special consideration is given to recent literature and management of the patient with repeat instability following surgery. Recent Findings Patellar stabilization surgery is in principle dependent upon restoration of normal patellofemoral anatomy and dynamic alignment. Historically, treatment opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 89 publications
(114 reference statements)
0
18
0
Order By: Relevance
“…One factor that is particularly important in this patient group is the status of the tibial and femoral physes [11]. While the surgical technique used for MPFL-R in this study does not usually affect the growth plate, there is still a slight risk.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…One factor that is particularly important in this patient group is the status of the tibial and femoral physes [11]. While the surgical technique used for MPFL-R in this study does not usually affect the growth plate, there is still a slight risk.…”
Section: Resultsmentioning
confidence: 90%
“…Physiotherapy also has an important role comprising quadriceps programs that focus on medial to lateral balance improvement as well as walking pattern re-education and jumping techniques [9,10]. If conservative management fails to improve the patients' symptoms signi cantly, surgical treatment is the next recommended step [11].…”
Section: Introductionmentioning
confidence: 99%
“…Assessing for increased patellar mobility is also helpful for clinical evaluation of patellar instability which causes other symptomatic issues outside of PT, such as patellofemoral pain and patellar subluxation/dislocation. These are common in pediatric patients who are often more flexible [30].…”
Section: Discussionmentioning
confidence: 99%
“…Medial patellofemoral ligament (MPFL) reconstruction has grown in popularity to become the method of choice in treating recurrent patellar dislocation (RPD). However, this growth has been accompanied by an increase in the number of novel operating techniques focussing on more targeted techniques that respond to anatomical abnormalities [1][2][3][4][5][6][7][8][9][10][11]. However, it is also important that isolated MPFL can be performed successfully regardless of the anatomical condition [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the treatment should include homogenous groups of patients with regard to their age and sexual maturity. It has been demonstrated that children prior to maturation are more exposed to the risk of redislocation and need to be treated with physeal-sparing methods [9,20].…”
Section: Introductionmentioning
confidence: 99%